Microbiological study of etiological pathogen in early infection of open fracture in orthopedics - Tai, Ken Meng (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
This study was conducted to evaluate the susceptibility of microorganism involved in early infection of open fractures in orthopaedics to current prophylactic antibiotics practice and determine the association of various characteristics to the resistance of such microorganism. The study was conducted from January 2015 to December 2017 in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. A total of 179 cases were collected from the operating record with 110 cases fulfilling the inclusion and exclusion criterias. They underwent routine debridement where culture and sensitivity were followed up. Previous notes were traced to identify the various risk factors involved and evaluated against resistance of microorganism. Admission to intensive care unit, blood transfusion, antibiotic regime and its' duration, fracture grade, injury severity score and duration of admission was significantly associated with resistance of microorganism. The study also demonstrated the predominance of Gram-negative microorganisms with 65.9%. Gram-negative microorganisms were seen more in higher fracture grades and Injury Severity Scale, and longer duration of admission or antibiotics prescribed. The overall susceptibility of microorganisms to antibiotics was also demonstrated with up to 68.6% resistance to cefuroxime and 36.9% to Gentamicin. Staphyloccoccus aureus and MRSA were the commonest Gram positive while Pseudomonas and Acinetobacter. The key words in this research are infected open fracture, microorganism and antibiotic resistance.